The possibilities of using data on national populations of fungal species to determine the Red List Category (based on the IUCN Criteria) - Kędra, Kamil (Acta Universitatis Lodziensis. Folia Biologica et Oecologica, 2014)
The paper refers to the current issue of determining the threat category for fungal species based on the widely used IUCN criteria and presents the information concerns the possible usability of data on populations of fungal species, especially macroscopic ones occuring in Poland, in order to make the best possible extinction risk assessment. The data is heterogeneous due to the various reasons, e.g. eneven mycological recognition of different parts of Poland. Therefore, the need to collect and analyze all currently available data for those taxa is urgent. The further discussion on the subject focusing on the development of a uniform national standard for such assessments is one of the most relevant issues for the near future. The arguments being presented in this paper are intented to be an additional voice in this discussion.